Kebijakan dan Strategi Pemerintah Kabupaten Bandung Barat dalam Penanggulangan Kemiskinan - Huraerah, Abu; Kurniasih, Nina; Suyono, Sinta Yulianti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2026)
Purpose of the study to analyze the policies and strategies of the West Bandung Regency Government in poverty alleviation. The research method used is a qualitative method. Data collection techniques used are unstructured interviews, focus group discussions, observations, and document studies. The results of the study indicate that several policies of the West Bandung Regency Government in poverty alleviation are manifested in the form of the West Bandung Regency Regent Regulation on Regional Action Plan (RAD/Rencana Aksi Daerah) for Poverty Alleviation, the West Bandung Regency Regional Regulation on the Implementation of Legal Aid for the Poor, the Regional Poverty Alleviation Plan (RPKD/Rencana Penanggulangan Kemiskinan Daerah) for 2025-2030, and specific policies in the program of